Random walk expectations and the forward discount puzzle - Bacchetta, Philippe 1960-; Van Wincoop, Eric (National Bureau of Economic Research, 2007)
Two well-known, but seemingly contradictory, features of exchange rates are that they are close to a random walk while at the same time exchange rate changes are predictable by interest rate differentials. In this paper we investigate whether these two features of the data may in fact be related. In particular, we ask whether the predictability of exchange rates by interest differentials naturally results when participants in the FX market adopt random walk expectations. We find that random walk expectations can explain the forward discount puzzle, but only if FX portfolio positions are revised infrequently. In contrast, with frequent portfolio adjustment and random walk expectations, we find that high interest rate currencies depreciate much more than what UIP would predict.
Literaturverz. S. 9